Detection of Different Properties of Ionospheric Perturbations in the Vicinity of the Korean Peninsula After the Hunga‐Tonga Volcanic Eruption on 15 January 2022 - Junseok Hong; Hyosub Kil; Woo Kyoung Lee; Young‐Sil Kwak; Byung‐Kyu Choi; Larry J. Paxton (Geophysical Research Letters)
Abstract This study reports different properties of ionospheric perturbations detected to the west and south of the Korean Peninsula after the Hunga‐Tonga volcanic eruption on 15 January 2022. Transient wave‐like total electron content (TEC) modulations and intense irregular TEC perturbations are detected in the west and south of the Korean Peninsula, respectively, about 8 hr after the eruption. The TEC modulations in the west propagate away from the epicenter with a speed of 302 m/s. Their occurrence time, propagation direction and velocity, and alignment with the surface air pressure perturbations indicate the generation of the TEC modulations by Lamb waves generated by the eruption. The strong TEC perturbations and L band scintillations in the south are interpreted in terms of the poleward extension of equatorial plasma bubbles (EPBs). We demonstrate the association of the EPBs with the volcanic eruption using the EPB occurrence climatology derived from Swarm satellite data.